2004
DOI: 10.1002/crat.200410275
|View full text |Cite
|
Sign up to set email alerts
|

Growth of lead bromide polycrystalline films

Abstract: Lead bromide polycrystalline films were grown by the physical vapor deposition method (PVD). Glass 1"x1" in size, uncoated, and coated with Indium Tin Oxide (ITO), was used as substrate and rear contact. The starting material was evaporated at temperatures from 395°C to 530°C under high vacuum atmosphere (6 x 10 -3 Pa) and during 8 days. The substrate temperature was prefixed from 190°C to 220°C. Film thickness yielded values from 40 to 90 µm. Optical microscopy and scanning electron microscopy (SEM) were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The crystallinity of these sample structures is verified by the XRD pattern, and the sharp peak of the as-prepared CH 3 NH 3 PbBr 3 MWs coordinated with a typical perovskite crystal structure with (001), (002), and (003) as well. , Typically, the PbBr 2 crystal structure shows the coordination structure, which is disturbed by hexagonal packing of bromine ions, and the lead ions are placed between them . It grows along a preferred orientation of the (00λ) planes . As shown in Figure d, the PbBr 2 MWs are well crystallized with (001) and (002) planes, which are also well matched with the CH 3 NH 3 PbBr 3 perovskite structure.…”
Section: Results and Discussionmentioning
confidence: 81%
“…The crystallinity of these sample structures is verified by the XRD pattern, and the sharp peak of the as-prepared CH 3 NH 3 PbBr 3 MWs coordinated with a typical perovskite crystal structure with (001), (002), and (003) as well. , Typically, the PbBr 2 crystal structure shows the coordination structure, which is disturbed by hexagonal packing of bromine ions, and the lead ions are placed between them . It grows along a preferred orientation of the (00λ) planes . As shown in Figure d, the PbBr 2 MWs are well crystallized with (001) and (002) planes, which are also well matched with the CH 3 NH 3 PbBr 3 perovskite structure.…”
Section: Results and Discussionmentioning
confidence: 81%
“…The temperature of the vessel was measured by sliding a Pt-PtRh thermocouple in a thin glass tube (3 mm in diameter) that was attached to the outer wall of the vessel. The source material of 4N PbBr 2 was melted at the bottom of the vessel (borosilicate glass tube of 10mm diameter) at 700 K in a vacuum of 10 -1 Pa and held there for various durations such as 10 min, 1,3,6,18,24,30,36,42,48, and 120 h.…”
Section: Methodsmentioning
confidence: 99%
“…PbBr 2 crystals have been grown from melt by Singh et al [1] and Kaito et al [2]. There are few papers on the vapour growth of PbBr 2 , except the paper by Giles et al [3], who grew a PbBr 2 film by the physical vapour deposition method. As reported in our previous paper [2], it is very difficult to grow a transparent PbBr 2 crystal from melt since the material has a strong tendency to be contaminated by the moisture in air.…”
Section: Introductionmentioning
confidence: 98%
“…Due to the high vapor pressure of these compounds below their melting point the physical vapor deposition method (PVD) emerged as suitable for growing such films at practical growth rates. Promising results have been reported for bismuth tri-iodide [15,16], lead iodide [12-14, mercuric iodide [7][8][9][10][11], lead bromide [17] and mercuric bromide-iodide [18] films. Research into AMFPI-based prototype imagers employing HgI 2 and PbI 2 have demonstrated potential for achieving high sensitivities and producing high quality x-ray images [8,19].…”
Section: Introductionmentioning
confidence: 91%